2005
DOI: 10.1097/01.ta.0000152549.63584.29
|View full text |Cite
|
Sign up to set email alerts
|

Spine Injuries Are Common Among Asymptomatic Patients After Gunshot Wounds

Abstract: Spine injuries without neurologic signs are not uncommon among patients with gunshot wounds. Complete radiographic spine imaging is therefore recommended to ensure that spine injuries are not missed in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…611 Data from the Vietnam conflict were retrospectively analysed and it was concluded that, in a hostile environment, only 1.4% of all casualties who were candidates for immobilisation may have benefited from this care and that, in this population, all penetrating cervical cord injury was universally fatal 7. In addition, Barkana et al 8 performed a retrospective chart review and evaluated autopsy reports of military casualties in Israel and concluded that life-threatening complications due to PNI (such as expanding haematomas) may be overlooked with a rigid cervical collar in place.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…611 Data from the Vietnam conflict were retrospectively analysed and it was concluded that, in a hostile environment, only 1.4% of all casualties who were candidates for immobilisation may have benefited from this care and that, in this population, all penetrating cervical cord injury was universally fatal 7. In addition, Barkana et al 8 performed a retrospective chart review and evaluated autopsy reports of military casualties in Israel and concluded that life-threatening complications due to PNI (such as expanding haematomas) may be overlooked with a rigid cervical collar in place.…”
Section: Resultsmentioning
confidence: 99%
“…A 10-year retrospective cohort study by Klein et al 6 reported that 33/183 patients (18%) with gun shot wounds to the neck had cervical spine injuries. The authors concluded that spine immobilisation is essential for patients with gunshot wounds to the neck until radiographic imaging is complete.…”
Section: Resultsmentioning
confidence: 99%
“…Upon further analysis, we found that the subset analyses of isolated head and isolated neck injuries may have been skewed by the findings of Klein et al, 24 which reviewed 2,450 patients with head, neck, and torso gunshot wounds (GSWs). This single-center study reported a higher incidence of spinal cord injuries (n = 244, 10%), and specifically unstable spine injuries (151 patients, 6.2%), than rates reported in other studies.…”
Section: Discussionmentioning
confidence: 94%
“…Two-thirds of the spine injuries are significant, and about 13% are unsuspected. 28 Plain radiographs and CT scans are helpful. The 3-column theory of Denis, 6 which meant for blunt trauma only, does not apply to penetrating trauma.…”
Section: Treatment Of Victims With No Neurologic Deficitmentioning
confidence: 98%